Development and calibration of a probabilistic finite element hip capsule representation. Issue 11 (17th August 2020) - Myers, Casey A.; Fitzpatrick, Clare K.; Huff, Daniel N.; Laz, Peter J.; Rullkoetter, Paul J.
Abstract: The objective of this study was to develop a probabilistic representation of the hip capsule, which is calibrated to experimental capsular torque-rotation behavior and captures the observed variability for use in population-based studies. A finite element model of the hip capsule was developed with structures composed of a fiber-reinforced membrane, represented by 2D quadrilateral elements embedded with tension-only non-linear spring. An average capsule representation was developed by calibrating ligament properties (linear stiffness, reference strain) so that torque-rotation behavior matched mean cadaveric data. A probabilistic capsule was produced by determining the ligament property variability which represented ±2 SD measured in the experiment. Differences between experimental and model kinematics across all positions had RMS error of 4.7°. Output bounds from the optimized probabilistic capsule representation were consistent with ±2 SD of experimental data; the overall RMS error was 5.1°. This model can be employed in population-based finite element studies of THA to assess mechanics in realistic scenarios considering implant design, as well as surgical and patient factors.